Hey shamieh.
I took a look at Wikipedia (I cheated on this one), but the key step is to use the fact that x! + x = 1 (where x is any variable).
Use algebraic manipulation to prove that xy + yz + x!z = xy + x!z (Note that this is the consensus property in section 2.5) [This is the property they are talking about: xy + yz + x!z = xy + x!z]
So I have:
xy + yz + x!z = xy + x!z
I'm lost.. Do they want me to factor? the left hand side first? or am I just making the left hand side look like the right y(x + z) + x!z? thus: yx +yz + x!z = xy + yz + x!z?
or do they want something like x(y + z) + x!
Is this correct?
Sham